Theory of Mind and Reading Comprehension in Deaf and Hard-of-Hearing Signing Children - Holmer, Emil; Heimann, Mikael; Rudner, Mary (Frontiers in Psychology, 2016)
Theory of Mind (ToM) is related to reading comprehension in hearing children. In the present study, we investigated progression in ToM in Swedish deaf and hard-of-hearing (DHH) signing children who were learning to read, as well as its assocation with reading comprehension. Thirteen children at Swedish state primary schools for DHH children performed a Swedish Sign Language (SSL) version of the Wellman and Liu (2004) ToM scale, along with tests of reading comprehension, SSL comprehension, and working memory. Results indicated that ToM progression did not differ from that reported in previous studies, although ToM development was delayed despite age-appropriate sign language skills. Correlation analysis revealed that ToM was associated with reading comprehension and working memory, but not sign language comprehension. We propose that some factor not investigated in the present study, possibly represented by inference making constrained by working memory capacity, supports both ToM and reading comprehension and may thus explain the results observed in the present study.